2009
DOI: 10.1371/journal.pone.0005035
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Membrane Protein Association in Model Membranes

Abstract: Membrane proteins are essential in the exchange processes of cells. In spite of great breakthrough in soluble proteins studies, membrane proteins structures, functions and interactions are still a challenge because of the difficulties related to their hydrophobic properties. Most of the experiments are performed with detergent-solubilized membrane proteins. However widely used micellar systems are far from the biological two-dimensions membrane. The development of new biomimetic membrane systems is fundamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 58 publications
3
63
0
Order By: Relevance
“…The crystal structure of the MexA in the lipid moiety-free form exhibited the six-or seven-membered twisted horseshoe assembly (21,22), which does not directly explain the MexA assembly in the membrane bound state. However, cryo-microscopic results in the reconstructed membrane layer showed that the MexA forms a hexameric complex with a dimension of 13-nm height (15,23,24). This finding is consistent with the hexameric model of MexA proposed in the previous report (14).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The crystal structure of the MexA in the lipid moiety-free form exhibited the six-or seven-membered twisted horseshoe assembly (21,22), which does not directly explain the MexA assembly in the membrane bound state. However, cryo-microscopic results in the reconstructed membrane layer showed that the MexA forms a hexameric complex with a dimension of 13-nm height (15,23,24). This finding is consistent with the hexameric model of MexA proposed in the previous report (14).…”
supporting
confidence: 92%
“…The hexameric MexA could be observed only when it anchors to the membrane and/or binds to OprM (15,23,24). To obtain the hexameric form of MexA, we initially attempted to determine the crystal structures of the complex of MexA and OprM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent crystallographic studies with the adapter MacA of the ATPdriven MacAB-TolC system suggests a MacA:TolC stoichiometry of 2, and the interactions appear to be much more stable compared with the AcrAB-TolC RND system in vitro and possibly also in vivo (16,17). Whether this stoichiometry is exclusive to this particular type of pump remains to be tested as well, because another very recent study (18) provides evidence for yet another 2:1 ratio between the MexA/OrpM subunits of the RND-type MexAB-OprM tripartite efflux pump from P. aeruginosa. Previous studies on AcrA, however, seem to be in accordance with its trimeric appearance (19).…”
Section: Cluster Of Excellence Macromolecular Complexes and Institutmentioning
confidence: 99%
“…Another significant advance in the study of component interaction was the in vitro examination of association between MexA and OprM (62). Such studies are difficult because both are membrane proteins (although some adaptor proteins appear to work in intact cells without the lipid modification at the N-terminus (52)), and the adaptor inserted into one membrane must interact with the OM channel inserted into another membrane (see Fig.…”
Section: Biochemical and Genetic Studiesmentioning
confidence: 99%